Fattigdom i Danmark: En socioøkonomisk fattigdomsgrænse - Iulian Vlad Serban (Luxembourg Income Study (LIS), 2011)
– The purpose of this project is to develop a quantitative model for poverty measurement in Denmark which takes into account social mobility and social heritage. As such the main goal is to define, measure and forecast the poverty development in Denmark, as well as identify and analyse the factors influencing poverty. Furthermore it is the purpose of this paper to inspire the academic fields working with poverty to use sophisticated quantitative statistical models to gain a more detailed picture of poverty. [...]
Keywords: 330